2021
DOI: 10.1055/a-1506-1627
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Five Alkaloids and their Metabolites in Normal and Diabetic Rats after Oral Administration of Rhizoma coptidis

Abstract: Rhizoma coptidis has been clinically used for a long time for the treatment of various diseases in China, such as hypertension, diabetes, and inflammation. Previous studies have shown that alkaloid components of Rhizoma coptidis extract could be extensively metabolized and the metabolites were also considered to be the therapeutic material basis. However, until now, pharmacokinetic studies of the in vivo metabolites have not been revealed yet. The aim of the present study was to characterize the pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Given that the comparative study of CC‐SF bio‐disposition in normal and colitis mice is lacking, our results can build a solid foundation for future study on the material basis and mechanism of CC‐SF in the treatment of colitis. In our study, the results from PCA indicated that the metabolism in UC was clearly different from that of the physiological condition, and the metabolism at 6 h after a dose may reflect the real colonic metabolism profile, which was in line with the literature [26]. The cluster heatmap analysis was consistent with the PCA and separated normal groups from colitis groups.…”
Section: Discussionsupporting
confidence: 89%
“…Given that the comparative study of CC‐SF bio‐disposition in normal and colitis mice is lacking, our results can build a solid foundation for future study on the material basis and mechanism of CC‐SF in the treatment of colitis. In our study, the results from PCA indicated that the metabolism in UC was clearly different from that of the physiological condition, and the metabolism at 6 h after a dose may reflect the real colonic metabolism profile, which was in line with the literature [26]. The cluster heatmap analysis was consistent with the PCA and separated normal groups from colitis groups.…”
Section: Discussionsupporting
confidence: 89%
“…It effectively reduces fasting plasma glucose, postprandial blood glucose, and glycosylated hemoglobin by participating in insulin resistance, anti-inflammatory, antioxidation, regulating lipid metabolism disorders and intestinal flora, and other methods. Berberine is mainly used in the treatment of type 2 diabetes, obesity, and metabolic diseases [ 21 27 ]. We detected berberine in plasma, feces, and biological samples, indicating that the prototype and metabolites of berberine are involved in the hypoglycemic mechanism.…”
Section: Discussionmentioning
confidence: 99%